Evaluation of ULS Bathymetry for Hydrodynamic Modelling - J. C. Haines; M. V. Peppa; C. Iliadis; J. P. Mills; V. Glenis; G. Mandlburger (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences)
The importance of accurate and reliable DTMs are paramount for hydrodynamic modelling. Currently, bathymetry is either not considered or a simpler mathematical representation of the river is created from observed cross sections for hydrodynamic models. Topographic and Bathymetric LiDAR creates centimetre resolution bathymetry and topography. However, it has not been applied into large scale hydrodynamic modelling. Following a major flood event in September 2024, a large fieldwork campaign on the Pielach River, Lower Austria, was conducted to capture the environmental changes using Topographic-Bathymetric LiDAR. Metre resolution DTMs of the bathymetric and topographic environment were created to produce flood inundation maps from crewed and uncrewed aerial mapping systems. Using the observed flow data of the September 2024 storm, resulting flood models prove the inclusion of bathymetry can produce reliable flood models with depths of greater than 6 m modelled. Due to the lower flying altitude and tactical flight paths of ULSs, it is possible to identify regions occluded by vegetation that would otherwise be overlooked by crewed Airborne Laser Scanning methods to produce more reliable flood models.